Phosphonate Decomposition-Induced Polyoxomolybdate Dumbbell-Type Cluster Formation: Structural Analysis, Proton Conduction, and Catalytic Sulfoxide Reduction - Armakola, Eirini; Salcedo, Inés R.; Bazaga-García, Montse; Mezei, Gellert; Cabeza-Díaz, Aurelio; Fernandes, Tiago A.; Kirillov, Alexander M.; Demadis, Konstantinos D. (ACS publications, 2019)
The reaction of MoO4^2− with a number of phosphonic acids [bis-(phosphonomethyl)glycine, R,S-hydroxyphosphonoacetic acid, 1-hydroxyethane-1,1-diphosphonic acid, phenylphosphonic acid, aminotris(methylene phosphonic acid), and 1,2- ethylenediphosphonic acid] under oxidizing (H2O2) hydrothermal conditions at low pH leads to rupture of the P−C bond, release of orthophosphate ions, and generation of the octanuclear, phosphate-bridged, polyoxometalate molybdenum cluster (NH4)5[Mo8(OH)2O24(μ8-PO4)](H2O)2 (POMPhos). This cluster has been fully characterized and its structure determined. It was studied as a proton conductor, giving moderate values of σ = 2.13 × 10−5 S·cm−1 (25 °C) and 1.17 × 10−4 S·cm−1 (80 °C) at 95% relative humidity, with Ea = 0.27 eV. The POMPhos cluster was then thermally treated at 310 °C, yielding (NH4)2.6(H3O)0.4(PO4Mo12O36) together with an amorphous impurity containing phosphate and molybdenum oxide. This product was also studied for its proton conductivity properties, giving rise to an impressively high value of σ = 2.43 × 10−3 S· cm−1 (25 °C) and 6.67 × 10−3 S·cm−1 (80 °C) at 95% relative humidity, 2 orders of magnitude higher than those corresponding to the “as-synthesized” solid. The utilization of POMPhos in catalytic reduction of different sulfoxides was also evaluated. POMPhos acts as an efficient homogeneous catalyst for the reduction of diphenyl sulfoxide to diphenyl sulfide, as a model reaction. Pinacol was used as a low-cost, environmentally friendly, and highly efficient reducing agent. The effects of different reaction parameters were investigated, namely the type of solvent and reducing agent, presence of acid promoter, reaction time and temperature, loading of catalyst and pinacol, allowing to achieve up to 84−99% yields of sulfide products under optimized conditions. Substrate scope was tested on the examples of diaryl, alkylaryl, dibenzyl, and dialkyl sulfoxides and excellent product yields were obtained.
Keywords: Conductividad eléctrica; Fósforo - Compuestos; Phosphate-bridged; Polyoxometalate molybdenum cluster; Proton-conductivity